Mitochondrial genome analysis in Passiflora - Abregu Olarte, Wendy Teresa (2023)
The genus Passiflora comprises approximately 525 species that represent a vast morphological diversity which serves as the basis for taxonomic classification into subgenera and sections. However, genomic studies are still emerging. Some initiatives have been developed to unravel the nuclear and organellar genome structure of some Passiflora species. So far, it can be said that plastid genomes (cpDNA) are better documented. Nevertheless, there is a lack of information on the mitochondrial genome (mtDNA), which should allow complementing evolutionary studies on the genus. Plant mtDNA shows remarkable variability in terms of genome size and structure, attributed to repetitive DNA sequences involved in homologous recombination and intracellular gene transfer (IGT). Regardless, despite its variability plant, mtDNA does not contain a large repertoire of genes. Instead, it maintains essential genes related to oxidative phosphorylation where the electron transport chain occurs. Our research group initially documented the mtDNA of P. organensis (subgenus Decaloba). In the present study, a hybrid assembly approach using short and long reads generated from Illumina and Oxford Nanopore technologies was employed to unravel the mtDNA of three Passiflora species: P. haematostigma (subgenus Astrophea), P. alata, and P. edulis (subgenus Passiflora). Our aim was to produce new genomic resources and generate knowledge that may be useful in evolutionary approaches to the genus. Despite our efforts, we were unable to capture a single circular molecule representing the \"master circle\". For P. haematostigma, three circular sequences with lengths of 275,820, 162,684, and 110,306 bp were identified. In contrast with P. edulis and P. alata, a single sequence with lengths of 737,209 and 693,479 bp, were respectively identified. These mtDNA genomes contain a conserved set of 32 protein-coding genes and 3 rRNA genes in the three species, accompanied by a variable number of tRNA genes ranging from 25 to 34. Interestingly, plastidial DNA insertion sites were observed in P. organensis and all three Passiflora species, ranging from ∽3 to ∽5%, highlighting the influence of IGT events on mtDNA size variation. These remarkable results on the structural and functional arrangement of Astrophea, Passiflora, and Decaloba mtDNAs suggest that further studies should be conducted to understand the possible relationship between the organization of mitochondrial genomes and the evolutionary patterns of the genus.